Y=x(9x-5)

Simple and best practice solution for Y=x(9x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y=x(9x-5) equation:



=Y(9Y-5)
We move all terms to the left:
-(Y(9Y-5))=0
We calculate terms in parentheses: -(Y(9Y-5)), so:
Y(9Y-5)
We multiply parentheses
9Y^2-5Y
Back to the equation:
-(9Y^2-5Y)
We get rid of parentheses
-9Y^2+5Y=0
a = -9; b = 5; c = 0;
Δ = b2-4ac
Δ = 52-4·(-9)·0
Δ = 25
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$Y_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$Y_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{25}=5$
$Y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(5)-5}{2*-9}=\frac{-10}{-18} =5/9 $
$Y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(5)+5}{2*-9}=\frac{0}{-18} =0 $

See similar equations:

| 2+10x=48x | | 4x-2=×+12 | | 4=-2(3x+1) | | F(3)=x²+3 | | 3{a-2}=36 | | 3(x+-5)+2(3x+1)=45 | | x=-5/24+3/8 | | 8(x-9)-9(x-8)=x+8-(x+2) | | 5=3-2x+5+5x | | 1/3(x+6)=-3 | | 6x-3+80=4x+3 | | 220=2x+4.4(5) | | -2x2-19x+18=0 | | -2x2-19+18=0 | | 3m-9•-1=24 | | 0.03(3t+3)=0.09(t+4)-0.27 | | -3+2,7x=0,7x+5 | | 6x-3+23=4x+3 | | 0.25=(80-x)/20 | | -4(x+1)/7+19=3(x-1) | | -1/4{x+2}+5=-x | | 3k×2=5 | | (x/5)-4=x/5 | | ?+?x3=14 | | 12b-42=7b+18.b= | | ?+?x3=16-2 | | (m+-8)(m+17)=0 | | 8.5=6.5{2d-3}=1 | | 10y-2=6y-30y+ | | 13y+25=0 | | 0.06(y-7)+0.02y=0.18y-0.3 | | 12b+19=7b+54.B= |

Equations solver categories